Pemanfaatan Media dan Teknologi Digital Dalam Mengatasi Masalah Pembelajaran Dimasa Pandemi - Yesi Arikarani; Muhammad Faizul Amirudin (STAI Bumi Silampari, 2021)
Digital or online learning is one of the right solutions in today's learning, the transformation from face to face (conventional) to online learning, all of which require understanding, skills and familiarity with online learning. Many problems were found in the use of media and digital technology applied in the first learning process, learning saturation, second, not following the learning process well. Third, not disciplined to do the task. This study aims to analyze various study concepts regarding the use of digital learning media and technology by analyzing using a literature review method that refers to theoretical studies and other references related to values, socio-culture and norms that develop in the social situation under study. The results of the analysis of the use of media and learning technology in overcoming problems during the pandemic are knowledge about the implementation of digital learning, blended learning models, online learning strategies, the accuracy of choosing LMS applications in digital learning and providing a contribution and prospect to online learning which is considered quite good and significantly improved in current learning.